Pars-plana fluid aspiration for positive vitreous cavity pressure in anterior segment surgeries - Kuriakose, Thomas (Indian J Ophthalmol, 2018)
Positive vitreous pressure due to misdirection of aqueous or choroidal effusion leads to shallowing of the anterior chamber (AC) before or during anterior segment surgeries. This shallow AC if not addressed makes surgery difficult and increases the risk of surgical complications. Methods to prevent and manage this condition described in literature are not without problems. We describe a minimally invasive technique of passing a 30G needle through the pars-plana to aspirate misdirected fluid from vitreous cavity either as a prophylaxis just before surgery or during it, thereby decreasing positive vitreous pressure. This technique, used in 12 eyes, seems to be effective in patients with angle-closure glaucoma, malignant glaucoma, and per-operative sudden increase in vitreous pressure during surgery. Small-incision surgeries are ideally suited for this procedure. This minimally invasive technique is simple to perform and complications are unlikely to be more than what is seen with intravitreal injections.